2010
DOI: 10.1121/1.3409481
|View full text |Cite
|
Sign up to set email alerts
|

On sound transmission loss across a Helmholtz resonator in a low Mach number flow duct

Abstract: A simplified physical model, which described the generation of sound by a Helmholtz resonator upon flow excitation at its neck, was developed in the present investigation to study the drop in sound power transmission loss across such a resonator mounted on the wall of a duct conveying a low Mach number mean flow. Experiments were derived to validate the model. Mitigation methods derived according to the model were also tested experimentally. Results showed that the simplified model gave predictions which agree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…The mean flow may induce tonal sound as indicated in existing literatures (such as Nelson et al 28 and Ziada et al, 29 but the narrow sidebranch tube width may weaken such lock-on effect. 7 These are left to further study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean flow may induce tonal sound as indicated in existing literatures (such as Nelson et al 28 and Ziada et al, 29 but the narrow sidebranch tube width may weaken such lock-on effect. 7 These are left to further study.…”
Section: Resultsmentioning
confidence: 99%
“…The Helmholtz resonators 7 and the plenum chambers 8 are typical examples. There are many derivatives proposed as well.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the grazing flow is evaluated and shown in Figure 5. It can be seen that the maximum TL 31 is decreased from 39 to 11 dB by approximately 28 dB, as the grazing flow Mach number is increased from 0 to 0.10, as the neck offset distance is set to five different values. The resonant frequency corresponding to the maximum TL is found to shift by approximately 10% to higher values with increased M u but less than 0.07.…”
Section: Resultsmentioning
confidence: 99%
“…Different authors [1][2][3][4][5][6][7][8] have studied two-and three-dimensional resonators under grazing flow using scale-resolving simulations such as Direct Numerical Simulation (DNS) and many experimental studies on Helmholtz resonators can be found in the literature. [9][10][11][12][13][14][15][16] It is shown that a Helmholtz resonator typically has a linear regime at low and moderate sound pressure levels (< 130dB). For this regime, it is expected that linearized governing equations can be used to model the acoustic behavior.…”
Section: Introductionmentioning
confidence: 99%
“…A few experimental studies on slit resonators exist, but they consider a relatively large perforation 16 or acoustic waves under normal incidence 3,6 . In order to provide the necessary validation data for the numerical simulations, a dedicated experimental campaign on a slit resonator under grazing flow has been carried out within the framework of this paper.…”
Section: Introductionmentioning
confidence: 99%